2006
DOI: 10.1158/1078-0432.ccr-06-0285
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Endothelial Delta-like 4 Expression Correlates with Vessel Maturation in Bladder Cancer

Abstract: Purpose: Angiogenesis and vascular endothelial growth factor (VEGF) expression are associated with a poor outcome in bladder cancer.To understand more about the mechanisms, we studied the role of delta-like 4 (DLL4), an endothelial-specific ligand of the Notch signaling pathway, in bladder cancer angiogenesis. Experimental Design: The expression of DLL4, CD34, and VEGF were studied in a cohort of 60 bladder tumors and 10 normal samples using quantitative PCR. In situ hybridization was used to study the pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
88
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 42 publications
(37 reference statements)
14
88
0
Order By: Relevance
“…Normal kidney did not express Dll4, but endothelial cells in renal cell carcinoma showed endothelial expression of Dll4, consistent with previous in situ hybridisation results (Supplementary Figures 1E and F) (Patel et al, 2005). Serial sections of bladder cancer showed endothelial colocalisation of Dll4 mRNA using in situ hybridisation (Patel et al, 2006), and protein using immunohistochemistry (Supplementary Figures 1D -F). …”
Section: Validation Of the Anti-dll4 Antibodysupporting
confidence: 89%
See 2 more Smart Citations
“…Normal kidney did not express Dll4, but endothelial cells in renal cell carcinoma showed endothelial expression of Dll4, consistent with previous in situ hybridisation results (Supplementary Figures 1E and F) (Patel et al, 2005). Serial sections of bladder cancer showed endothelial colocalisation of Dll4 mRNA using in situ hybridisation (Patel et al, 2006), and protein using immunohistochemistry (Supplementary Figures 1D -F). …”
Section: Validation Of the Anti-dll4 Antibodysupporting
confidence: 89%
“…This is consistent with data from human xenografts (Noguera-Troise et al, 2006) and in situ hybridisation data for Dll4 in human bladder cancer (Patel et al, 2006) and human renal cell carcinoma (Mailhos et al, 2001;Patel et al, 2005). The lack of expression of Dll4 in the endothelial cells and epithelium of normal colonic crypts is consistent with the lack of VEGF expression by normal colorectal mucosa (Jubb et al, 2003) and the lack of intestinal toxicity and goblet cell hyperplasia observed in anti-Dll4-treated mice (Ridgway et al, 2006).…”
Section: Spatial Regulation Of An Appropriate Level Of Dll4 Expressiosupporting
confidence: 87%
See 1 more Smart Citation
“…Suggesting that the important role of Dll4 and Notch signaling is not restricted to only developmental angiogenesis, Dll4 is prominently expressed in tumor blood vessels in a VEGF-dependent fashion (Patel et al 2005(Patel et al , 2006Hainaud et al 2006;Noguera-Troise et al 2006). Indeed, blockade of Dll4-Notch signaling with the Dll4/Fc antagonist, anti-Dll4 antibodies, or ␥-secretase inhibitor promotes endothelial sprouting and thereby increases vascular density in xenograft tumor models in mice (Noguera-Troise et al 2006;Ridgway et al 2006;Scehnet et al 2007).…”
Section: Notch and Vascular Morphogenesis Genes And Development 2519mentioning
confidence: 99%
“…The Notch pathway was implicated in tumor angiogenesis when the human Notch ligand Delta-like 4 (DLL4) was found to be up-regulated in tumor blood vessels in several types of cancer (Mailhos et al 2001;Patel et al 2005;Patel et al 2006). Given the Notch pathway's close association with the VEGF pathway, it was thought that this up-regulation might somehow contribute to VEGF-independent angiogenesis, and several groups subsequently investigated the effects of Dll4 inhibition on physiological angiogenesis in mouse models.…”
Section: Tips Stalks and Tubesmentioning
confidence: 99%